2020
DOI: 10.3390/cells9010247
|View full text |Cite
|
Sign up to set email alerts
|

AXL Controls Directed Migration of Mesenchymal Triple-Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) is an aggressive form of breast cancer with high risk of relapse and metastasis. TNBC is a heterogeneous disease comprising different molecular subtypes including those with mesenchymal features. The tyrosine kinase AXL is expressed in mesenchymal cells and plays a role in drug resistance, migration and metastasis. We confirm that AXL is more expressed in mesenchymal TNBC cells compared to luminal breast cancer cells, and that its invalidation impairs cell migration while h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 77 publications
1
25
0
Order By: Relevance
“…4K). These results correlate with the recent work by Zajac et al showing the presence of AXL in LAMP1-positive vesicles in mammary tumor cells 33 . Besides, we found in flotillin-positive late endosomes other signaling transmembrane receptors and oncogenic molecules that participate in tumorigenesis, such as EphA4 and TGFβ (fig.…”
Section: Resultssupporting
confidence: 92%
“…4K). These results correlate with the recent work by Zajac et al showing the presence of AXL in LAMP1-positive vesicles in mammary tumor cells 33 . Besides, we found in flotillin-positive late endosomes other signaling transmembrane receptors and oncogenic molecules that participate in tumorigenesis, such as EphA4 and TGFβ (fig.…”
Section: Resultssupporting
confidence: 92%
“…Accordingly, we found that AXL was accumulated in actin-rich cell regions, including lamellipodia, in glioblastoma LN229 cells. Similarly, a very recent study of Zajac et al (2020) showed that AXL colocalized with F-actin at the leading edge of migrating mesenchymal triple-negative breast cancer cells, and its depletion impaired the directionality of cell migration (Zajac et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…In Glioblastoma cells expressing high basal levels of Axl induced by GAS6, the knockdown of Axl led to reduced response to sunitinib (multi-targeted TKI) by rescuing migration [43]. In mesenchymal triple-negative breast cancer cells, Axl is localized to the Golgi apparatus and the leading edge of the migrating cell [44]. This polarization at the leading edge can be displaced by the Axl inhibitor, R438 and may indicate that Axl controls directed cell migration [44].…”
Section: Invasion and Migrationmentioning
confidence: 99%